Juridical Problems of Ministers' Administrative Authority in the Determination of Domain Name Registrars in Indonesia - Andi Budimansyah; Akmal Syaddad; Frida Junariah; Indri Lestari; Siti Fajri Ilaika (LUTUR Law Journal, 2026)
Domain name governance is no longer solely a technical issue of internet addressing, but has become part of the legal infrastructure of digital identity, cybersecurity, consumer protection, and digital sovereignty of the state. In Indonesia, Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions normatively recognizes Registry and Registrar as domain name managers. However, in practice, formal designation by the Minister seems to be given to the Indonesian Internet Domain Name Manager as the ".id" State Domain Registry, while the Registrar operates mainly through an accreditation mechanism or private agreement with the Indonesian Internet Domain Name Manager. This article examines the legal gap between normative construction and administrative practice in the determination of Registrars in Indonesia. This study uses a normative juridical method with a legislative approach, a conceptual approach, and an analytical approach. The results of the study show that the absence of a direct determination by the Minister to the Registrar creates legal uncertainty, weakens administrative supervision, limits consumer protection for Registrants, and reduces the effectiveness of cybersecurity governance at the domain registration level. This article argues that the Minister's appointment of the Registrar should not be seen as a bureaucratic obstacle, but rather as a public legal instrument to strengthen accountability, legal certainty, and digital sovereignty. Therefore, a special arrangement is needed that integrates the determination of the Registrar with a proportionate, risk-based, and digitized supervision mechanism.